Effect of pyrite packed thickness on its oxidation pathway in high temperature. Issue 1 (31st December 2023) - Liu, Jinting; Zhang, Weifang; Chen, Xiaoduo; Huang, Zijian; Fu, Xiaoheng; Wang, Chunli
ABSTRACT: In this work, the packed thickness of pyrite's effect on its conversion behavior and kinetics was investigated under air in high temperatures. The results showed that pyrite was oxidized to hematite directly with no more than 2 mm packed thickness, or indirect oxidation occurred (pyrite → pyrrhotite → hematite) when greater than 2 mm. Subsequently, the evolutions of pyrite were studied comprehensively by X-ray diffraction (XRD), Raman, Scanning electron microscope (SEM), and Transmission electron microscopy (TEM). The kinetics by the Avrami – Erofeev method displayed that the activation energy of the process of pyrite → hematite (27 KJ·mol −1 ) < pyrite → pyrrhotite (34 KJ·mol −1 ) < pyrrhotite → hematite (42 KJ·mol −1 ). The thinner-packed pyrite requires less energy to oxidize and more readily undergoes direct oxidation. The thermodynamics theoretically explained the reasons for indirect/direct oxidation of thicker-packed/thinner-packed pyrite that ΔGpyrrhotite < ΔGhematite in the thicker packed, or ΔGpyrrhotite > ΔGhematite in the thinner packed. This paper provided some fundamental and significant knowledge of pyrite oxidation to reduce SO2 emissions and industrial production safety.